Circulating immune complexes, serum immunoglobulins, and acute phase proteins in psoriasis and psoriatic arthritis. Issue 1 (February 1981) - Laurent, M R; Panayi, G S; Shepherd, P
Abstract : Raised levels of circulating immune complexes were found in the plasma of 47% of patients with psoriasis and in 58% of those with psoriatic arthritis. The mean levels were significantly raised when compared with normals, but there was no difference between the 2 patient groups. The levels of acute phase proteins (C-reactive protein, fibrinogen, alpha-1-antitrypsin, and the 9th component of complement) were normal in those patients with psoriasis but were significantly raised in patients with psoriatic arthritis. Serum immunoglobulin G and A levels were equally raised in both patient groups, immunoglobulin M being normal. C-reactive protein and fibrinogen gave the best correlation with the clinical index of disease activity.